Bakteri Endofit dari Tanaman Kehutanan sebagai Pemacu Pertumbuhan Tanaman Tomat dan Agens Pengendali Meloidogyne sp. - Abdul Munif; Arif Rafi Wibowo; Elis Nina Herliyana (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Meloidogyne sp. is one of the main constraints of tomato production in Indonesia. Endophytic bacteria may be considered as biocontrol agents for controlling Meloidogyne sp. The objective of this study was to isolate endophytic bacteria from forestry plants and to evaluate its potential for controling Meloidogyne sp. on tomato. Endophytic bacteria were isolated from roots of mahoni (Swietenia mahogany), trambesi (Albizia saman), gaharu (Aquilaria malacensis), and meranti (Shorea sp.). Isolation of bacterial endophytes from plant tissue was conducted using surface sterilization method with 70% alcohol, 3% NaOCl and sterile water on medium trypsic soy agar. Endophytic bacteria was separated and purified based on shape and color of the colony. A total of 33 isolates of endophytic bacteria were isolated from roots of mahoni (11 isolates), trambesi (5 isolates), gaharu (7 isolates), and meranti (10 isolates). The bacteria was tested for the hypersensitivity reaction on tobacco plants and the result showed that 22 isolates did not cause necrosis, indicated they are not pathogenic. Ten isolates of endophytic bacteria was selected for further experiment, i.e. to evaluate their potential as biocontrol agent for Meloidogyne sp. and as growth promotor for tomato plants. The experiment was conducted in the screenhouse using seed treatment. The result showed that two isolates of endophytic bacteria, i.e. MSJ1H and AGS1F were able to increase the growth of tomato plants up to 60% and reduce the number of root knot caused by Meloidogyne sp. Endophytic bacteria isolated from forestry plants have the potential as a biocontrol agents to plant parasitic nematode Meloidogyne sp.